Isocyanide-Based Multicomponent [2+2+1]-Cycloaddition Strategy to Construct Functionalized Spirocyclic Oxindoles - Jie, Haohua; Li, Jian; Li, Chunju; Jia, Xueshun (Synlett, 2012)
Isocyanide-based three-component [2+2+1]-cycloaddition reactions from isocyanides, activated alkynes, and isatylidene malononitriles were investigated to provide a new access to spirocyclic oxindole with five-membered carbon rings. The displacement of isatylidene malononitrile with oxindolylideneacetate essentially results in opposite regioselectivity, which adds to its attractiveness.
Keywords: isocyanide; activated alkyne; isatylidene malononitrile; spirocyclic oxindole; oxindolylideneacetate